(untitled) (Universal International Scientific Journal, 2026)
This study evaluates the effectiveness of the “SAN.GAY-1” special mobile simulator in improving the physical fitness of high school students during extracurricular activities. A system of high-intensity exercises was implemented during the study. The results showed improvements in students’ explosive power and speed, as well as a reduction in the risk of injuries. The mobile and flexible design of the simulator allows its effective use in educational institutions.